2021
DOI: 10.1101/2021.10.31.21265714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Azithromycin consumption during the COVID-19 pandemic in Croatia, 2020

Abstract: BackgroundDuring the initial phase of the COVID-19 pandemic, there was great enthusiasm for the use of azithromycin with or without hydroxychloroquine.ObjectivesWe analyzed azithromycin consumption in Croatia in 2020 and compared this to the period 2017–2019.MethodsAzithromycin consumption was evaluated using the IQVIA Adriatic d.o.o. database which collects data on azithromycin distribution from wholesale pharmacies to hospital and non-hospital pharmacies in Croatia. We analyzed data for the period from Janua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Many clinical studies have shown that the use of azithromycin did not have any positive effect in the treatment of patients with COVID-19 infection (Del Fiol et al, 2022). In the newer version of the guidelines for the treatment of patients with COVID-19, strong recommendations were made against the use of azithromycin alone and azithromycin in combination with hydroxychloroquine and colchicine (Bogdanić et al, 2022;Del Fiol et al, 2022;Roche et al, 2022). Regarding inpatient settings, the hospital list of restricted antibiotics that require an approval from the designated infection control team when used consists of 15 antibiotics (piperacillin/ tazobactam, cefuroxime, ceftazidime, ceftriaxone, cefotaxime, cefepime, imipenem/cilastatin, meropenem, ertrapenem, vancomycin, colistin, clarithromycin, moxifloxacin, ciprofloxacin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have shown that the use of azithromycin did not have any positive effect in the treatment of patients with COVID-19 infection (Del Fiol et al, 2022). In the newer version of the guidelines for the treatment of patients with COVID-19, strong recommendations were made against the use of azithromycin alone and azithromycin in combination with hydroxychloroquine and colchicine (Bogdanić et al, 2022;Del Fiol et al, 2022;Roche et al, 2022). Regarding inpatient settings, the hospital list of restricted antibiotics that require an approval from the designated infection control team when used consists of 15 antibiotics (piperacillin/ tazobactam, cefuroxime, ceftazidime, ceftriaxone, cefotaxime, cefepime, imipenem/cilastatin, meropenem, ertrapenem, vancomycin, colistin, clarithromycin, moxifloxacin, ciprofloxacin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for treatment of COVID-19 issued by the Croatian Ministry of Health and the European Medical Agency in late 2020 did not include administration of empirical antibiotics ( 8 , 9 ). Despite the guidelines, latest data available in Croatia show an increase in the prescription of azithromycin in clear correlation with the increase of COVID-19 patients ( 10 ). However, reported rates of bacterial co-infections in COVID-19 patients are low.…”
mentioning
confidence: 99%
“…Furthermore, while overall prescribing may have decreased, prescription of specific antibiotics has increased, particularly those associated with COVID-19 prophylaxis. For instance, community consumption of azithromycin increased during the first year of the pandemic in multiple countries [48][49][50]. Several studies have now characterized the wide range of antibiotics provided as prophylaxis to both mild and severe COVID-19 patients in 2020 [51,52], though it remains unclear to what extent prophylaxis is appropriate for prevention of bacterial coinfection in COVID-19 patients, particularly for mild cases treated in the community.…”
Section: Discussionmentioning
confidence: 99%